2016
DOI: 10.18632/oncotarget.9216
|View full text |Cite
|
Sign up to set email alerts
|

Targeting miR-21-3p inhibits proliferation and invasion of ovarian cancer cells

Abstract: MicroRNA-21 is overexpressed in most cancers and has been implicated in tumorigenesis. Accumulating evidence supports a central role for the miR-21 guide strand (miR-21-5p) in ovarian cancer initiation, progression, and chemoresistance. However, there is limited information regarding the biological role of the miR-21 passenger strand (miR-21-3p) in ovarian cancer cells. The aim of this study was to investigate the role of miR-21-3p and its target genes in cisplatin-resistant ovarian cancer cells. Expression pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 35 publications
5
72
0
Order By: Relevance
“…ZNF608 is associated with transcriptional events [221]. By inhibiting those three downstream targets, miR-21-3p contributes to tumorigenesis and CSC proliferation [222]. In the cervical cancer cell lines Hela, CaSki, Siha, and C33A, miR-23b decreases the tumorsphere amount and size, suppresses stem marker expression, and decreases cell resistance to cisplastin via inhibition of the expression of aldehyde dehydrogenase 1 family member A1 (ALDHA1) [223].…”
Section: Discussionmentioning
confidence: 99%
“…ZNF608 is associated with transcriptional events [221]. By inhibiting those three downstream targets, miR-21-3p contributes to tumorigenesis and CSC proliferation [222]. In the cervical cancer cell lines Hela, CaSki, Siha, and C33A, miR-23b decreases the tumorsphere amount and size, suppresses stem marker expression, and decreases cell resistance to cisplastin via inhibition of the expression of aldehyde dehydrogenase 1 family member A1 (ALDHA1) [223].…”
Section: Discussionmentioning
confidence: 99%
“…The miR-17-92 cluster, an oncomiR, presents a high frequency of genomic alterations [123] and it induces angiogenesis through inhibition of thrombospondin 1 [124]. miR-21, an oncomir, regulates Phosphatase and tensin homolog (PTEN), this enzyme acts as a tumor suppressor [125], it has an inverse relation with programmed cell death protein 4 (PDCD4) expression [126] and it exerts an inhibitory effect on cancer cell proliferation [127]. This miR has also been associated with recurrence-free survival, which will be lower if miR-21 levels are elevated [128].…”
Section: Role Of Mirs In Ovarian Cancermentioning
confidence: 99%
“…Previous studies reported that the overexpression of miR‐21 is associated with the invasion and metastasis of various human cancer cells . Therefore, in order to determine whether miR‐21‐3p was necessary for cell invasion and migration, transwell assay and wound healing assay were performed to detect the invasive as well as migratory abilities of the HCT116 cells, respectively, following transfection with miR‐21‐3p inhibitors or NC‐miRNA.…”
Section: Resultsmentioning
confidence: 99%